Bank lines of credit as a source of long-term finance - Chang, Xin (2023)
Hand-collecting credit line drawdowns that firms classify as long-Term debt, we first document how long-Term drawdowns rise with high investment needs or weak external capital market conditions. Nearly all drawdown proceeds finance long-Term investment, including M&A activity. Unrated and lower-rated firms rely more on long-Term drawdowns than high or very poorly rated firms. We further find that credit lines have tighter covenants than terms loans. Drawdowns are repaid fairly quickly and often refinanced with other long-Term debt. Our findings support the monitored liquidity insurance theory of credit lines and highlight that longterm drawdowns act as a valuable bridge financing mechanism.